Consumer acceptance of nutritional dates seed innovation for a new ice cream flavor in Malaysia - Mahmod, Razmah; Saad, Mazni; Mashahadi, Faizah; Mohamed Sayuti, Nazura (Penerbit UNIMAP, 2021)
Date fruit is a type of fruit grown mainly in the eastern region. Favourable research findings on date nutritional value have led to dates becoming one of the well-known fruits consumed by many people worldwide. In general, people only consume the date flesh but throw the seed as waste. Recent studies have indicated nutritional benefits in date seed with potential health benefits for human beings. In relation to promoting a green environment, this study examines consumer acceptance of the innovation of nutritional dates seed powder as the main ingredient in producing a new ice-cream flavour in Malaysia and determines the dates' nutrient content seed ice-cream mixture. The survey questions were adapted from the Nielsen Global New Product Innovation Survey, Q1 2015, distributed through the Google form application. Of the 301 respondents randomly chosen, 94% agreed that dates seed ice cream was an innovative food with nutritional value. In contrast, 84.7% were interested in buying the ice cream if it was available in the market. The descriptive analysis indicated that the respondents accepted dates seed ice cream as a new ice-cream flavour with nutritional benefits. In determining the nutrient content of the seeds of the dates in the ice cream, a sample of the ice-cream mixture was sent to the SIRIM QAS laboratory for chemical analysis in August 2018. The findings showed that dates seed ice cream has a high nutrient content and calorie value, and since it contains no caffeine, it can be a substitute for coffee.